2005
DOI: 10.1091/mbc.e04-05-0400
|View full text |Cite
|
Sign up to set email alerts
|

An Internal Motor Kinesin Is Associated with the Golgi Apparatus and Plays a Role in Trichome Morphogenesis inArabidopsis

Abstract: Members of the kinesin superfamily are microtubule-based motor proteins that transport molecules/organelles along microtubules. We have identified similar internal motor kinesins, Kinesin-13A, from the cotton Gossypium hirsutum and Arabidopsis thaliana. Their motor domains share high degree of similarity with those of internal motor kinesins of animals and protists in the MCAK/Kinesin13 subfamily. However, no significant sequence similarities were detected in sequences outside the motor domain. In Arabidopsis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
138
3
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(148 citation statements)
references
References 62 publications
6
138
3
1
Order By: Relevance
“…Although our experiments revealed that Kinsein-13A promotes microtubule depolymerization both in vitro and in vivo, previous articles reported that Kinesin-13A does not localize to cortical microtubules (Lu et al, 2005;Wei et al, 2009). We hypothesized that this apparent discrepancy is attributable to the absence or presence of MIDD1, which may contribute to the targeting of Kinesin-13a to microtubules in vivo.…”
Section: Kinesin-13a Requires Midd1 For the Depolymerization Of Corticontrasting
confidence: 60%
See 1 more Smart Citation
“…Although our experiments revealed that Kinsein-13A promotes microtubule depolymerization both in vitro and in vivo, previous articles reported that Kinesin-13A does not localize to cortical microtubules (Lu et al, 2005;Wei et al, 2009). We hypothesized that this apparent discrepancy is attributable to the absence or presence of MIDD1, which may contribute to the targeting of Kinesin-13a to microtubules in vivo.…”
Section: Kinesin-13a Requires Midd1 For the Depolymerization Of Corticontrasting
confidence: 60%
“…In animals, members of the kinesin-13 family have microtubule depolymerization activity (Desai et al, 1999;Moores and Milligan, 2006). Although Kinesin-13A is involved in trichome morphogenesis (Lu et al, 2005), its molecular function in plant cells is currently unclear. In this study, we investigated the function of Kinesin-13A in metaxylem vessel cells.…”
Section: Introductionmentioning
confidence: 99%
“…The extensive bundles of endoplasmic microtubules of agd1 mutants could also explain the abnormal Golgi movement at the root hair tip. In this regard, it was shown that Golgi stacks can interact with both microtubules and actin and that certain kinesins facilitate the dispersal of Golgi stacks in plant cells (Lu et al, 2005). Since ark1 root hairs exhibited bundled arrays of F-actin at the tip similar to agd1, both AGD1 and ARK1 may have common downstream targets that regulate cytoskeletal dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Shimmen [2007] has recently reviewed the 50 years of research establishing that the main motive force of cytoplasmic streaming is generated by the sliding of organelle-associated myosin XI along actin filaments. Although microtubules and their associated motors also contribute to intracellular movements in higher plant cells, they appear to be involved in short-distance movement and positioning of organelles at the cell cortex, rather than in long-distance or fast streaming [Van Gestel et al, 2002;Romagnoli et al, 2003Romagnoli et al, , 2007Lu et al, 2005].…”
Section: Actin Bundles In Cytoplasmic Streaming and Transvacuolar Strmentioning
confidence: 99%